ANALISIS KESALAHAN KALIMAT TEKS EKSPLANASI SISWA KELAS VII SMP NEGERI 12 PADANG - Deosy, Rara Fadhila; Abdurahman, Abdurahman; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2016)
ABSTRACTÂ This study aimed to describe the error text sentences of explanation students in terms of aspects (1) improper use of effective sentence, (2) misuse of word choice, and (3) ketepataan spelling (capital letters , the use of punctuation , and spelling ) . The research was a qualitative descriptive method . The data source of this research is explanatory text of the seventh grade students of SMPN 12 Padang academic year 2015/2016 . Data of this research is the wrong sentence . Based on the results obtained the following data . First , in terms of syntax errors syntactic structures such as fault location subject. Second , word choice errors in the form of a pronoun (pronoun) is not appropriate , and the details are not exact words . Third, the exact spelling ( capital letters , spelling , punctuation and usage) .Â Kata kunci: kesalahan kalimat, teks eksplanasi